Numerical Semantics and Cultural Cognition: Investigating the Symbolic Value of Numbers in Russian and English Linguoculture - Zhazira , Zhauynshiyeva; Kurmambayeva , Zhuldyz; Tanat , Ayapova; Turlybekov , Berdibay; Gaukhar , Yersultanova (Journal of Ecohumanism, 2025)
This research paper explores the role of numerical codes in the linguocultures of Russian and English, focusing on their semantics and symbolism. Numerical codes, which include figures such as "three," "seven," "ten," and others, hold distinct meanings and cultural connotations that vary between languages and societies. This study examines how these numbers are used in proverbs, idiomatic expressions, folklore, and everyday language, with an emphasis on their symbolic value. In particular, the paper contrasts the interpretations and uses of numerical codes in Russian and English-speaking cultures, seeking to understand the cultural nuances behind these symbols. It also addresses the psychological and cognitive underpinnings that shape these codes, proposing that numbers are not merely utilitarian markers but also reflect deeper cultural values, beliefs, and traditions. Through a combination of literary analysis and cognitive linguistics, this paper sheds light on how numbers function within the broader framework of cultural identity and communication.